Granulocyte transfusions for treating infections in people with neutropenia or neutrophil dysfunction - Estcourt, L; Stanworth, S; Hopewell, S; Doree, C; Trivella, M; Massey, E (Wiley: Cochrane Collaboration, 2016)
Background Despite modern antimicrobials and supportive therapy bacterial and fungal infections are still major complications in people with prolonged disease-related or treatment-related neutropenia. Transfusions of granulocytes have a long history of usage in clinical practice to support and treat severe infection in high-risk groups of patients with neutropenia or neutrophil dysfunction. However, there is considerable current variability in therapeutic granulocyte transfusion practice, and uncertainty about the beneficial effect of transfusions given as an adjunct to antibiotics on mortality. This is an update of a Cochrane review first published in 2005. Objectives To determine the effectiveness and safety of granulocyte transfusions compared to no granulocyte transfusions as adjuncts to antimicrobials for treating infections in people with neutropenia or disorders of neutrophil function aimed at reducing mortality and other adverse outcomes related to infection. Search methods We searched for randomised controlled trials (RCTs) in the Cochrane Central Register of Controlled Trials (CENTRAL) (the Cochrane Library 2016, Issue 2). MEDLINE (from 1946), Embase (from 1974), CINAHL (from 1937), the Transfusion Evidence Library (from 1980) and ongoing trial databases to 11 February 2016. Selection criteria RCTs comparing people with neutropenia or disorders of neutrophil dysfunction receiving granulocyte transfusions to treat infection with a control group receiving no granulocyte transfusions. Neonates are the subject of another Cochrane review and were excluded from this review. There was no restriction by outcomes examined, language or publication status. Data collection and analysis We used standard methodological procedures expected by the Cochrane Collaboration. Main results We identified 10 trials that met the inclusion criteria with a total of 587 participants. We also identified another ongoing trial. These trials were conducted between 1975 and 2015. None of the studies included people with neutrophil dysfunction. The studies differed in the type of infections they included. Six studies included both children and adults, however data were not reported separately for children and adults. The two newest studies gave granulocyte colony stimulating factor (G-CSF) to donors; both were stopped early due to lack of recruitment. Three studies re-randomised participants and therefore quantitative analysis was unable to be performed. Overall the quality of the evidence was very low to low across different outcomes according to GRADE methodology. This was due to many of the studies being at high risk of bias, and many of the outcomes being imprecise. There may be no difference in all-cause mortality over 30 days between participants receiving therapeutic granulocyte transfusions and those that did not (six studies; 321 participants; RR 0.75, 95% CI 0.54 to 1.04; very low-quality evidence). There were no differences between the granulocyte dose subgroups (< 1 x 1010 per day versus ≥ 1 x 1010 per day) (test for subgroup differences P = 0.39). There was a difference in all-cause mortality between the studies based on the age of the study (published before 2000 versus published 2000 or later) (test for subgroup differences P = 0.03). There was no difference in all-cause mortality between participants receiving granulocyte transfusions and those that did not in the newest study (one study; 111 participants; RR 1.10, 95% CI 0.70 to 1.73, low-quality evidence). There may be a reduction in all-cause mortality in participants receiving granulocyte transfusions compared to those that did not in studies published before the year 2000 (five studies; 210 participants; RR 0.53, 95% CI 0.33 to 0.85; low-quality evidence). There may be no difference in clinical reversal of concurrent infection between participants receiving therapeutic granulocyte transfusions and those that did not (five studies; 286 participants; RR 0.98, 95% CI 0.81 to 1.19; low-quality evidence). There is insufficient evidence to determine whether there is a difference in pulmonary serious adverse events (1 study; 24 participants; RR 0.85, 95% CI 0.38 to 1.88; very low-quality evidence). None of the studies reported number of days on therapeutic antibiotics, number of adverse events requiring discontinuation of treatment, or quality of life. Six studies reported their funding sources and all were funded by governments or charities. Authors' conclusions In people who are neutropenic due to myelosuppressive chemotherapy or a haematopoietic stem cell transplant, there is insufficient evidence to determine whether granulocyte transfusions affect all-cause mortality. To be able to detect a decrease in all-cause mortality from 35% to 30% would require a study containing at least 2748 participants (80% power, 5% significance). There is low-grade evidence that therapeutic granulocyte transfusions may not increase the number of participants with clinical resolution of an infection.